Metode Monofilamen Test dan Ipswich Touch Test (IPTT) untuk Deteksi Neuropati Sensorik Diabetes - Dahrizal, Dahrizal; Idramsyah, Idramsyah; Revalina, Revalina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe the monofilament test and Ipswich touch test methods for screening diabetic sensory neuropathy. The research method used is a literature study of research articles published in national and international journals in 2020-2023 using the Scopus, Science Direct, PubMed, and Google Scholar databases. The results of this study identified ten research articles that explained that 10g monofilament is the most widely used diabetic sensory neuropathy screening tool because it is simpler, more objective, and easier to use. The Ipswich Touch Test is the most straightforward inspection technique that can be carried out without using tools. In conclusion, both methods proved effective in detecting diabetic sensory neuropathy, although differences in sensitivity and specificity of the two methods require further research. Keywords: Ipswich Touch Test, Monofilament Test, Diabetic Neuropathy, Sensory Neuropathy